Effects of a Motivational Climate on Psychological Needs Satisfaction, Motivation and Commitment in Teen Handball Players - Alesi, Marianna (2019)
The aim of this study was to examine the effects of the motivational climate created by the coach and perceived by a group of young high-performance handball players on their sport motivation, self-determination, sport psychological needs and sport commitment. The study participants were 479 young handball players. The age range was 16-17 years old. Players were administered a battery composed of a Perceived Motivational Climate in Sport Questionnaire, Sport Motivation Scale, the Basic Psychological Needs in Exercise Scale and Sport Commitment Questionnaire to measure the above-mentioned theoretical constructs. Results showed that the handball players showed high levels of a task-involving climate, of basic psychological needs satisfaction and of self-determined motivation and commitment. Higher levels of basic psychological needs such as autonomy and competence were associated with a higher task-involving climate, self-determined index and sport commitment (task-involving climate-basic psychological needs (β = 0.55; 95% IC 0.387/0.682; p = 0.001); Ego-involving climate-basic psychological needs (β = 0.06; 95% IC -0.069/0.181; p = 0.387); Basic psychological needs-self-determined index (β = 0.48; 95% IC 0.376/0.571; p = 0.001); Self-determined index-commitment (β = 0.58; 95% IC 0.488/0.663; p = 0.001). The obtained model showed that basic psychological needs mediated the association between a task-involving climate and self-determination, and self-determination mediated the association between basic psychological needs satisfaction and commitment.